Diagnostic Accuracy of 3-Dimensional Ultrasound in Mullerian Duct Anomalies in Comparison to MRI - Mehtab, Ghazal; Afzal, Arooj; Aamir, Muhammad Riaz; Nawaz, Samia; Rashid, Adnan; Ahmad, Irshad (Indus Journal of Bioscience Research, 2025)
Introduction: Müllerian duct anomalies (MDAs) are the congenital anomalies of female reproductive tract that can have significant impact on a woman’s fertility and her pregnancy outcomes. Accurate imaging is essential for their diagnosis and management. 2-dimensional ultrasound (2D US) and MRI are the traditional methods that have been mainstays for the diagnosing purpose, but the introduction of 3D Ultrasound in the domain of ultrasound has offered potential advantages in visualization and enhancing diagnostic accuracy. Objective: To find out what is the diagnostic accuracy of 3-Dimensional ultrasound in diagnosing Mullerian duct anomalies as compared to MRI. Materials and Methodology: Articles included in this review were identified through systematic searches of databases such as Pub Med, Paywall, Wiley.com and Google Scholar. Studies were selected based on their relevance to the use of 3D ultrasound in diagnosing Müllerian duct anomalies. Results: Based on different studies we found that 3 Dimensional Ultrasound proved to be highly accurate in diagnosis of Uterine anomalies and showed strong agreement with MRI(P <0.01). Conclusion: 3D ultrasound has proved to be an excellent modality for the diagnosis of mullerian duct modalities. It’s low cost, easy access and real time imaging make it promising and a good diagnosing tool. Although MRI is the standard reference, 3D ultrasound can be preffered over it if its limitations are minimized as the diagnostic accuracy is almost similar to MRI if performed by experienced hands.